TVET UNiTY programme helps Parit Sulong community - Noor Syahidah, Sabran (2022)
PARIT SULONG, 30 October 2022 - The organisation of TVET UNiTY@Parit Sulong Programme has successfully helped the community through technical expertise sharing in engineering, research service and social science in improving their well-being and socioeconomic status.